2013
DOI: 10.1002/hed.23404
|View full text |Cite
|
Sign up to set email alerts
|

CXC motif ligand 12 as a novel diagnostic marker for papillary thyroid carcinoma

Abstract: Our findings indicate that CXCL12 might serve as an effective novel supplementary diagnostic marker for PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In the present study, CK19 seemed to be the weakest marker, as it exhibited the lowest specificity and AUC with respect to diagnosing PTC, likely because its expression rate is extremely high in both benign and malignant thyroid tissue. This finding is consistent with that of a study by Chung et al (30). Previous studies have A and B).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, CK19 seemed to be the weakest marker, as it exhibited the lowest specificity and AUC with respect to diagnosing PTC, likely because its expression rate is extremely high in both benign and malignant thyroid tissue. This finding is consistent with that of a study by Chung et al (30). Previous studies have A and B).…”
Section: Discussionsupporting
confidence: 94%
“…These findings indicate that CXCL12 may be an effective biomarker for PTC. Consistently, Chung et al ( 20 ) recently demonstrated that CXCL12 was exclusively overexpressed in human PTC regardless of histological subtypes compared with non-cancerous thyroid lesions, and the sensitivity and specificity of using CXCL12 as a diagnostic marker for PTC was 90.8 and 96.8%, respectively ( 20 ). Jung et al ( 21 ) also reported that 90% of follicular PTC specimens were positive for CXCL12, whereas only 10.5% of follicular thyroid neoplasm specimens showed positive CXCL12.…”
Section: Discussionmentioning
confidence: 72%
“…Strong CXCR7 expression has been found in tumor-associated blood vessels in breast and lung cancer tissue but not on normal vasculature ( 19 ). In thyroid cancer, the expressions of CXCL12, CXCR4 and CXCR7 have also been detected in cancer tissue ( 20 23 ). However, the contribution of CXCL12/CXCR4/CXCR7 axis to thyroid cancer progression and the possible CXCR4-mediated signaling pathways in thyroid cancer cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CXC motif ligand 12, also known as stromal cell-derived factor-1, binds to the CXCR4 ( 39 ) and to the CXCR7 receptors ( 59 , 60 ). CXCL12 displays a strong chemotactic power toward lymphocytes, and it is known to play an important role in angiogenesis and tumor cell migration ( 39 ). The expression of CXCL12, CXCR4, and CXCR7 was detected in thyroid cancer tissue specimens ( 39 , 61 63 ).…”
Section: Thyroid Cancermentioning
confidence: 99%